2018
DOI: 10.1016/j.cr.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoiesis and microenvironment in hematological malignancies

Abstract: Adult hematopoietic stem cells (HSCs) and progenitors (HPCs) reside in the bone marrow, a highly orchestrated architecture. In the bone marrow, the process of how HSCs exert self-renewal and differentiation is tightly regulated by the surrounding microenvironment, or niche. Recent advances in imaging technologies and numerous knockout or knockin mouse models have greatly improved our understanding of the organization of the bone marrow niche. This niche compartment includes a complex network of mesenchymal ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…In addition to cellular communication, exosomes are known to be associated with immune reactions, cancer viability and invasion, antigen presentation, and cell migration and differentiation (53). Recently, a number of studies have demonstrated the role of these EVs in hematological malignancies (21)(22)(23), as well as their involvement at different diseases phases (33,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cellular communication, exosomes are known to be associated with immune reactions, cancer viability and invasion, antigen presentation, and cell migration and differentiation (53). Recently, a number of studies have demonstrated the role of these EVs in hematological malignancies (21)(22)(23), as well as their involvement at different diseases phases (33,53).…”
Section: Discussionmentioning
confidence: 99%
“…currently, at least to the best of our knowledge, there are no studies available reporting the possibility of enriching the tumor-derived exosome fraction in patients affected by different types of leukemia. However, certain groups have revealed that exosomes isolated from cell line cultures modulate the crosstalk between leukemia cells and the bone marrow (BM) microenvironment, and that they also carry molecular tumor markers (21)(22)(23)(24). Moreover, recent studies have indicated that leukemia-derived exosomes can be utilized as prognostic (25), diagnostic (26) and therapeutic biomarkers (27) for individuals suffering from different hematologic malignancies, such as acute myeloid leukemia (28)(29)(30), multiple myeloma (31) and chronic lymphocytic leukemia (32).…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoiesis is a precisely modulated multi-step process including hematopoietic stem cell (HSC) selfrenewal and hematopoietic stem/progenitor cell differentiation [1,2]. Erythropoiesis and megakaryopoiesis are important parts of hematopoiesis [3,4]. Normal erythropoiesis produces about 10 11 new red blood cells (RBCs) every day in an adult human through the commitment of hematopoietic stem cells into erythroid progenitors, which subsequently differentiate into mature RBCs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Different cytokines achieves this transformati on through variety pathways and thereby mediates LSC mobilization, homing and drug resistance, which eventually become an important cause of clinical recurrence (9). Treatment to hijacked or transformed niches may provide no vel therapies to delay the leukemia relapse (10).…”
Section: Introductionmentioning
confidence: 99%